IMPROVEMENT OF METHODS FOR MANAGING LAND AREA QUANTITY AND QUALITY USING GEOSPATIAL ANALYSIS TECHNOLOGIES - Akhmedova Muhayyo Shavkatovna (TADQIQOTLAR, 2025)
Abstract:  The  rapid  advancement  of  geospatial  analysis  technologies  has transformed  land  management  practices  by  offering  precise  and  efficient  tools  for monitoring land area quantity and quality. This study explores the integration of key geospatial  technologies—Remote  Sensing  (RS),  Geographic  Information  Systems (GIS), Artificial Intelligence (AI), and the Internet of Things (IoT)—in improving land assessment  and  sustainable  resource  management.  Through  a  detailed  analysis  of current methods, we identify how these technologies enhance soil classification, land cover  monitoring,  and  urban  planning.  Furthermore,  the  paper  addresses  existing challenges,  including  data  integration  complexities  and  the  need  for  standardized methodologies. Our findings suggest that combining geospatial technologies with AI-driven  analysis  improves  accuracy,  efficiency,  and  long-term  land  management strategies. This study contributes to the ongoing discourse on sustainable land use, offering  insights  for  policymakers  and  researchers  aiming  to  optimize  geospatial practices.